PENINGKATAN KEMAMPUAN MEMBACA TEKS EKSPOSISI MELALUI METODE COOPERATIVE INTEGRATED READING AND COMPOSITION SISWA MTS - Agasasmita, Susan; Martono, Martono; Abdussamad, Abdussamad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was motivated by the low reading comprehension ability to 8th grade students of Mts Islamiyah.The method used in this study was descriptive method with clasroom action research. The data source in this study were teacher and 26 pupils 8th grade of MTs Islamiyah Pontianak. The data in this study were in the form of document RPP and the results of tests conducted by students about the ability to reading comprehension of exposition text by using a method of cooperative integrated reading and compositon. The data collection techniques used are direct observation techniques.Planning cycle The average average score of planning cycle I was 98,6 and cycle the score obtained reaches 100. In the implementation of cycle 1 learning the average value reaches 81,25 and of cycle 2 increased with the average value 98,9. Then on cycle 1 learning outcomes by using a method of cooperative integrated reading and composition pupils learning have increased by an average was 50,7. Then in cycle 2 pupils learning outcomes again increased by an average was 75,2.Conclusion in this study was method of cooperative intergated reading and compositon both used in reading text eksposition skills because it can help pupils work together in group learning because the group division was heterogeneous. Keywords:Ability, Reading Text Eksposition, The Method of Cooperative IntegratedÂ Â  Reading and Compositon.